Forecast of export of transportation services - Koroleva, Anna A.; Dutina, Alina A. (Journal of the Belarusian State University. Economics, 2018)
The article analyses the current state of Belarusian logistical system. The authors discovered the factors having the greatest influence on the increase (reduction) of transportation services export volume and determined the development trends of Belarusian transport segment. Based on the research results a mathematical model describing adequately the transportation services segment was built, and a forecast of development of such services till 2030 has been made.